Model Information Utilization Report, Blue-Action Case Study Nr. 1 (D5.2) - Contreras, Gonzalez Roxana Patricia Gabriela; Mettiäinen, Ilona; Toivonen, Jusu; Coath, Martin (Zenodo, 2018)
Northern Finland is one of the fastest warming regions in Europe with the greatest increases in temperature being seen in November, December and January. For the winter tourism sector, proper winter conditions are key to commercial success: information on future climate and specific local weather conditions is fundamental for preparing and adapting to future change. Long-term business planning for Northern Finnish winter tourism industry therefore needs to account for the increased likelihood of the October-December season being too warm and plan for alternatives to winter sports. Forecast data is required to plan for the next season, especially at the beginning of the season with the need for snow making and snow storage and plan mid-term operations and investments that allow their businesses to adapt to the changing and variable climate (semi-decadal scale). Furthermore, weather and climate information is required to assess the competitive position of Northern Finland relative to other major European Ski Centres. The task of this case study in Blue-Action WP5 is to “assess the value of improved weather and climate predictions for short-term and mid-term planning of operations for ski centres in Northern Finland”. In this deliverable D5.2, Model Information Utilization Report, a general procedure for generating and delivering data and associated uncertainties in a format useful for the Rukakeskus Ltd (Ruka). company, the end-user of this case study, is presented. This procedure has been developed in collaboration between the case study (CS1) participants: Arctic Centre, University of Lapland (AC UoL) and Rukakeskus Ltd (Ruka). Blue-Action - Arctic Impact on Weather and Climate (727852) (EU Horizon2020)